1996
DOI: 10.1111/j.1468-3148.1996.tb00119.x
|View full text |Cite
|
Sign up to set email alerts
|

The Move from Hospital: A Long‐Term Follow‐up of Challenging Behaviour Levels

Abstract: Levels of challenging behaviour were studied in a sample of 16 people who moved from a hospital to community settings. Ratings on the Challenging Behaviour Scales showed that aggression to residents decreased significantly. Aggression to staff and self-injurious behaviour showed non-significant downward trends but destruction of objects continued at prior levels. The study concluded that caution needs to be taken in using rating scales, and results from them should always be backed up by other evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…It is now well understood that these people can and do experience mental health problems, and may in fact be more vulnerable than the general population (Hamlin and Oakes, 2008). While the transition had a number of specific benefits, such as reduction in self-injurious behaviour and aggression (Collins and Halman, 1996) and an increase in social interaction (Dagnan et al, 1998), an expectation that it would reduce mental health and behavioural problems more generally soon proved unfounded (Chaplin et al, 2010). Indeed, the transition often caused additional problems, such as relocation syndrome (Bouras et al, 1993), in which people became depressed and more isolated, and problem behaviours increased (Chaplin et al, 2010).…”
Section: Mental Health Problems In People With Intellectual Disabilitiesmentioning
confidence: 99%
“…It is now well understood that these people can and do experience mental health problems, and may in fact be more vulnerable than the general population (Hamlin and Oakes, 2008). While the transition had a number of specific benefits, such as reduction in self-injurious behaviour and aggression (Collins and Halman, 1996) and an increase in social interaction (Dagnan et al, 1998), an expectation that it would reduce mental health and behavioural problems more generally soon proved unfounded (Chaplin et al, 2010). Indeed, the transition often caused additional problems, such as relocation syndrome (Bouras et al, 1993), in which people became depressed and more isolated, and problem behaviours increased (Chaplin et al, 2010).…”
Section: Mental Health Problems In People With Intellectual Disabilitiesmentioning
confidence: 99%
“…Lowe & Felce (1995) discussed the importance of assessing challenging behaviours in terms of their real impact and consequences, and working towards a consensus view of which types of behaviour are typically cited as being severely challenging. Collins & Halman (1996) summarized the difficulties in measuring challenging behaviour, and suggested that scales which consider the frequency and impact of behaviour are more useful than inventories since both of these will give some indication of likely consequences.…”
Section: Introductionmentioning
confidence: 99%